Boraginaceae plant fragment as a foreign body in the lacrimal duct: Multidisciplinary diagnosis - ÇETİNBAŞ GENÇ, ASLIHAN; VARDAR, FİLİZ (My University, 2024)
Foreign bodies in the lacrimal drainage system pose a substantial challenge in clinical practice due to their potential morbidity and diverse origins. Many foreign bodies are inorganic; however, organic foreign bodies, although uncommon, present diagnostic challenges. We present the case of a 57-year-old woman who had epiphora in her right eye. Patient\"s physical examination suggested an obstruction in the nasolacrimal duct. An external dacryocystorhinostomy (DCR) was scheduled. The surgery uncovered a polyp-like intrasaccal structure, which was subsequently identified as an organic foreign body through a comprehensive histopathological examination. This case underscores the significance of precise histopathological evaluation, multidisciplinary collaboration, and meticulous assessment in the identification of uncommon intraorbital organic foreign bodies.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Göz Hastalıkları; Clinical Medicine (Med); Clinical Medicine; Ophthalmology; Oftalmoloji; Lacrimal duct; nasolacrimal duct obstruction; organic foreign body; vegetal origin